THE ROLE OF THE ENTERPRISE'S INTERNAL CONTROL SYSTEM AND RISK REDUCTION - Ishmanova Dinara; Shohjahon Usmanbekov (Science, education, innovation: modern tasks and prospects, 2025)
In a market economy, the internal control system plays an important role in ensuring the stability and efficiency of enterprises. The internal control system allows you to control financial, organizational and production processes within the enterprise, eliminate identified shortcomings, and identify and reduce risks in advance. This system serves to rationally use the enterprise's resources, ensure the reliability of accounting data, and improve the quality of management decisions made by management. In recent years, increased competition, rapid changes in market demands, and external economic factors have further increased the attention of enterprises to the internal control system. In particular, the introduction of digital technologies, the use of automated control mechanisms, and the modernization of risk assessment methods are becoming one of the most pressing issues today. Therefore, improving the internal control system of an enterprise and combining it with risk reduction are of great importance in ensuring the financial stability of the enterprise, preventing errors and fraud, and establishing effective management.